MOLECULAR GENETIC AND IMMUNOLOGICAL ASPECTS OF INVASIVE ASPERGILLOSIS - O. V. Shadrivova; E. V. Frolova; A. Е. Taraskina; N. N. Klimko (Журнал инфектологии, 2017)
Aspergillus is very widely spread in nature. Daily people inhale to several thousand spores of micromycetes, however, an effective immune response prevents to development of the disease. In case of violation the mechanisms of innate and adaptive immune response as a result of genetic defects or iatrogenic immunosuppression Aspergillus spp. become pathogenic and can cause severe invasive infections in immunocompromised patients. Until now there are no reliable biomarkers for the risk prediction of invasive aspergillosis and monitoring the effectiveness of treatment of infectious process. In our review, we are considering the most important genetic and immunological factors affecting susceptibility to Aspergillus spp., The analysis of which can provide an individual approach to antifungal therapy / prevention in immunocompromised patients.